Influence of Occupants’ Space and Appliance Use Patterns and Behaviour during the Discomfort on Electricity Consumption in Mixed Mode Residences - Sivapriya Chelliah; Subbaiyan G; Srinivas Tadepalli (International Journal of Sustainable Construction Engineering and Technology, 2023)
Building characteristics, climate, socio-economic characteristics, and occupant behaviour influence the electricity consumption in buildings. In residential buildings, where people spend a lot of time and have high perceived control over their surroundings, electricity consumption for thermal comfort constitutes a higher proportion of overall energy consumption. Previous research studies mainly focused on the impact of building and household characteristics on electricity consumption in residences. In the Indian context, electricity usage in residential buildings may depend on lifestyle, family composition, daily routines and activity patterns, and consumption habits. In India, the space usage and sharing pattern of internal spaces depend on family composition and the number of rooms. In India, the usage of household appliances has been steadily increasing. During discomfort hours in humid conditions, people use fans with windows in the open position, switch on the air-conditioner or use the fan and air-conditioner together to attain thermal comfort. Therefore, the study aims to assess the impact of family composition, occupants' space and appliance use patterns and behaviour during the thermal discomfort on electricity consumption in Indian residential buildings. Information on the number of occupants, children, and elders; space usage at different hours of the day by the occupants; use of fans, air-conditioners, and other electrical appliances; and frequency and hours of opening of windows were collected through a questionnaire survey from 144 residences. Electricity consumption data for all 144 residences were collected from the utility bills. The variables influencing annual mean electricity consumption per unit area of residential buildings include the number of elders present, age of children, hours of air-conditioner use, space usage pattern, and occupants' behaviour during the discomfort.